(3GdGSJOQGcs - (3GHf ofbWI GdMfHdj GdHZOGOj , eMeO Hf YHO GdZfj Hf CHj HcQ Hf TLGY, eYjf GdOjf, GHf ofbWI , CHh HcQ J (B629 (3g` s
(3ChdgG (B:s
(3hGYde habc Gddg ddNjQGJ Cfi fXQJ ai cJGH GdCejQ CHj fUQ Ydi Hf gHI Gddg Hf Ydi Hf LYaQ GdMGaX GdeYQha HGHf eGchdG s
(3BNQgG (B:s
(3ai WHbGJ Cgd gePGf hbGd Qhi Yfg GdMSf Hf jRjO GdObjbi hcGf UhbGeGJ bHd GdYTQ hKdGK eGjI s
(3Pjd Ydi GdEceGd dCHi fUQ Hf eGchdGs
(3fSNI ai BNQgG SeGYGJ SfI (B659s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B179s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B358 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/1 - (3U (B12 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs